State failure, governance failure and policy failure: Exploring the linkages. (July 2015) - Peters, B Guy
There is some tendency to lump together policy failures arising from different sources and having different fundamental characteristics. This is a problem conceptually, as well as for building effective theory about policy failure, but it can also be a practical difficulty for policymakers if they fail to differentiate these various possible roots of failure. This paper explores the linkages among these types of failure within the public sector.